A Test of the Expected Utility Model: Evidence from Earthquake Risks - Brookshire, David S.; Thayer, Mark A.; Tschirhart, John; Schulze, William D. (Journal of Political Economy, 1985)
The purposes of this paper are twofold. The first is to demonstrate that the expected utility hypothesis is a reasonable description of behavior for consumers who face a low-probability, high-loss natural hazard event, given that they have adequate information. The second is to demonstrate that in California information non earthquake hazards was generated by a 1974 state law that created a market for safe housing that previously did not exist.